ANALYSIS OF ACOUSTIC PATH TRANSMISSION FACTOR FOR ANGULAR VELOCITY SENSOR - Durukan, Ya; Peregudov, A. N.; Shevelko, M. M. (Izvestiâ vysših učebnyh zavedenij Rossii. Radioèlektronika, 2019)
The change in characteristics of ultrasonic waves’ transmittion in solid rotating media is the basis for the operation of acoustic angular velocity sensor. The transmission coefficient of the sensing element (SE) of the acoustic path deter-mines the level of angular velocity sensor informative signal based on detecting changes in characteristics of bulk acoustic waves in solid media. In this regard, the efforts aimed at obtaining maximum transmission coefficient are relevant and represent an important stage in the design of such devices. The sensitive element of the acoustic path consists of radiating and receiving plate piezoelectric transducers, propagation medium (acoustic duct), contact layers and electrical load. The coefficient is identical to the path of ultrasonic delay lines on bulk acoustic waves. Although, many sources present the theoretical analysis of the path of this type, they carry out the analysis in so-called one-dimensional approximation, i.e. they perform the analysis without taking into account the limited transverse dimensions, whereas the path of the sensing element should have limited lateral dimensions, which can affect the value of transmission coefficient. The above-mentioned sources do not present the results of experiments. Thus, it is necessary to conduct a complex of simulation and experiments to analyze the acoustic path transmission coefficient of the angular velocity sensor. Authors of the paper developed a pathmodeling program in Mathcad software to perform simulation. For implementation of the experiment, authors created the installation, as well as a number of proto-types with transducers made of piezoelectric quartz and piezoelectric ceramics. The results demonstrate that fundamental statements developed for one-dimensional approximation one can use to determine the transmission coefficient of the acoustic path with limited dimensions. Besides, the use of the matched electrical load gives the opportunity to increase the transmission coefficient. For example, in case of Y-cut piezoelectric quartz converter prototype the increase reached 20 dB.